2018
DOI: 10.1080/17512433.2018.1510312
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2A6 gene polymorphism on the pharmacokinetics of dexmedetomidine for premedication

Abstract: In Chinese patients pretreated with dexmedetomidine, T was consistent with that published, but T, V and Cl were lower. It was unnecessary to consider the mutation when developing the precision regimen of dexmedetomidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…According to the well stirred liver model, liver blood flow and not enzyme activity is the main determinant of clearance for high extraction ratio drugs. This reasoning is supported by experimental work by Kohli et al 22 and Wang et al, 23 who observed no influence of CYP2A6 metabolizer status on dexmedetomidine pharmacokinetics.…”
Section: Dexmedetomidine Elicits Nonlinear Kineticsmentioning
confidence: 62%
“…According to the well stirred liver model, liver blood flow and not enzyme activity is the main determinant of clearance for high extraction ratio drugs. This reasoning is supported by experimental work by Kohli et al 22 and Wang et al, 23 who observed no influence of CYP2A6 metabolizer status on dexmedetomidine pharmacokinetics.…”
Section: Dexmedetomidine Elicits Nonlinear Kineticsmentioning
confidence: 62%
“…Unfortunately, there is a lack of information on personalized medicine involving dexmedetomidine. Previous studies have demonstrated that no significant pharmacokinetic differences were observed among genetic variations in CYP2A6 (Utkarsh et al, ; Wang et al, ). However, population differences exist in the frequencies of different CYP2A6 alleles in Asian and Caucasian populations (Carter et al, ; Utkarsh et al, ).…”
Section: Resultsmentioning
confidence: 94%
“…Because of the paucity of substrates, the significance of genetic variations in CYP2A6 has not been well understood. Findings from other studies have shown that the gene variations in CYP2A6 had no significant influence on the pharmacokinetics of dexmedetomidine (Utkarsh et al, ; Wang et al, ). However, certain factors including inadequate samples, a combination of medications and the complex pathophysiological conditions still impact the results.…”
Section: Introductionmentioning
confidence: 93%
“…Mycophenolate mofetil was administered from POD 14–21 (daily doses of 2 g). The details of the immunosuppression protocol and standard surgical techniques used in this study have been described previously [ 24 , 25 , 26 ]. We do not routinely remove the spleen and preserve the middle hepatic vein for donors.…”
Section: Methodsmentioning
confidence: 99%